Breakthroughs in Cathode Materials for Solid Oxide Fuel Cells: A Review of Recent Advances (Comprehensive Journal of Science, 2025)
Solid Oxide Fuel Cells (SOFCs) represent a cutting-edge electrochemical technology that effectively transforms chemical energy from fuels into electrical energy, providing high efficiency, flexibility in fuel use, and reduced pollutant emissions. However, the high operational temperatures have traditionally limited their commercialization due to intricate system configurations and material degradation. Recent studies have shifted focus toward lowering operating temperatures to sub-600°C and within the intermediate range of 600-850°C, which reduces thermal stress and costs but introduces challenges such as delayed reaction kinetics and heightened ohmic losses. This report offers a summary of notable progress in SOFC materials over the last ten years, emphasizing advancements in cathode materials. Cathode materials are vital to the performance of Solid Oxide Fuel Cells (SOFCs) as they directly influence the efficiency of the oxygen reduction reaction (ORR). This report centers on the developments and innovations in cathode materials, particularly lanthanum manganite (LMO), lanthanum strontium cobalt oxide (LSCO), and barium strontium cobalt ferrite (BSCF). LMO, particularly when doped with strontium, provides stability and compatibility with yttria-stabilized zirconia (YSZ) electrolytes, though its conductivity may be restricted. LSCO is notable for its outstanding electrical conductivity and catalytic performance, making it a top candidate for SOFC applications, but it encounters challenges related to oxidation and long-term durability. BSCF showcases remarkable mixed ionic-electronic conductivity and ORR activity, making it a compelling option for intermediate-temperature SOFCs, although concerns regarding cobalt’s expense and environmental effect persist. Current research is focused on improving these materials' performance through innovative synthesis techniques, doping methods, and composite designs, ultimately advancing the commercialization and efficiency of SOFC technology within sustainable energy frameworks.
Keywords: Solid Oxide Fuel Cells (SOFCs), cathode materials, operating temperature, oxygen reduction reaction (ORR), electrical conductivity and sustainability